Pendampingan Company Visit Mahasiswa ke Kantor Akuntan Publik PKF Hadiwinata & Partners Jakarta - Ahmad Basid Hasibuan; Agustina Indriani; Atik Isniawati; Radina Modjaningrat; Saminem Saminem (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
essential for fostering the motivation to enhance their professional competencies. The primary objective of these visits is to bridge the gap between classroom theory and its practical application within the business and industrial sectors. Through these visits, students are expected to gain insights into fundamental concepts, business processes, governance structures, work cultures, and operational regulations. For universities, the business and industrial sectors represent key partners in supporting the